Conductas disruptivas y el desarrollo del lenguaje en un niño con discapacidad intelectual - Severino Ramos, Saida Elizabeth; Rivera Angamarca, Mariuxi Viviana (Machala: Universidad Técnica de Machala, 2024)
The research project addresses the influence of disruptive behaviours on the language development of a child with intellectual disabilities.The research problem focuses on determining how disruptive behaviours affect language development. The general objective is to analyse this influence, based on John B. Watson's behaviourist theory and Vygotsky's socio-cultural theory. For data collection, several instruments were used: an observation guide to record specific behaviours of the child, a structured interview with parents and educators to obtain qualitative information about the child's behaviour and linguistic development, the BASC test to assess disruptive behaviours. The results show a significant correlation between disruptive behaviours and difficulties in language development. The data indicate that an environment with high rates of disruptive behaviour can hinder the acquisition and development of language skills, affecting both comprehension and verbal expression. This study highlights the need for integrated interventions that address both disruptive behaviours and language development, proposing strategies based on Watson's and Vygotsky's theories to improve children's educational and emotional outcomes
El trabajo de titulación aborda la influencia de las conductas disruptivas en el desarrollo del lenguaje de un niño con discapacidad intelectual. El problema de investigación se centra en determinar cómo las conductas disruptivas afectan dicho desarrollo. El objetivo general es analizar esta influencia, sustentado en la teoría conductista de John B. Watson y la teoría sociocultural de Vygotsky. Para la recopilación de datos, se emplearon varios instrumentos: una guía de observación para registrar comportamientos específicos del niño, una entrevista estructurada con los padres y educadores para obtener información cualitativa sobre su comportamiento y desarrollo lingüístico, el test BASC para evaluar las conductas disruptivas. Los resultados muestran una correlación significativa entre las conductas disruptivas y las dificultades en el desarrollo del lenguaje. Los datos indican que un ambiente con altas tasas de conducta disruptiva puede obstaculizar la adquisición y el desarrollo de habilidades lingüísticas, afectando tanto la comprensión como la expresión verbal. Este estudio destaca la necesidad de intervenciones integradas que aborden tanto las conductas disruptivas como el desarrollo del lenguaje, proponiendo estrategias basadas en las teorías de Watson y Vygotsky para mejorar los resultados educativos y emocionales del niño.
Keywords: LENGUAJE; DISCAPACIDAD INTELECTUAL; CONDUCTA DISRUPTIVA; TEORIA CONDUCTISTA